2021
DOI: 10.1080/14992027.2021.1933621
|View full text |Cite
|
Sign up to set email alerts
|

Critical hearing experiences manifest differently across individuals: insights from hearing aid data captured in real-life moments

Abstract: Objective: We investigated whether contrasts between situations of good and difficult listening experiences could be identified in objective hearing aid (HA) data, with the aim to use these insights for personalisation of hearing care. Design: The participants were asked to fill out an ecological momentary assessment (EMA) report every time they encountered a good or difficult listening experience for a period of two weeks. During EMA reporting, the participants described their listening environment and why it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…satisfaction 16 and as such, we do not consider one method to be superior to the other in this aspect, but rather want to discuss their potential of complementing each other. For example, "Focused Listening -Live Sounds" was rated by participants in EMA, whereas only one participant in HEARLI-Q indicated such situations to occur on daily or weekly basis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…satisfaction 16 and as such, we do not consider one method to be superior to the other in this aspect, but rather want to discuss their potential of complementing each other. For example, "Focused Listening -Live Sounds" was rated by participants in EMA, whereas only one participant in HEARLI-Q indicated such situations to occur on daily or weekly basis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Consequently, certain situations are underrepresented in EMA 9,10 . Participants may also be less likely to interact with the EMA application in a moment that is already challenging 11 and these situations are often the most interesting when evaluating HAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In real-life, listeners often report vastly different experiences and/or hearing aid expectation, warranting the need for a more comprehensive understanding of unique auditory lifestyles. 30 This sought after and rich relationship between the acoustical environments experienced in everyday life and the perceptual demands of individual listeners in these environments has been termed "auditory ecology." 31,32 Auditory ecology is integral to achieving personalized and objective hearing care planning.…”
Section: Personalizing Care With Acoustic Ecologymentioning
confidence: 99%
“…Many measures to improve the listening situation also increase the SNR and previous studies have indicated that people spend most time in easy listening situations without much noise (4,8,9,10). Another reason for high satisfaction / benefit ratings could be that EMA questionnaires do not capture difficult situations as participants are less inclined to interact with the study equipment and answer a survey in a situation that is already challenging for them (11). There could also be personal reasons for the high ratings, such as, wanting to please the experimenter in cases where a hearing aid / fitting is being evaluated by the hearing aid manufacturer or the participant's hearing care provider.…”
Section: Introductionmentioning
confidence: 99%